English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

do I put 3a in place of x?

2007-05-25 07:49:15 · 6 answers · asked by lois g 2 in Science & Mathematics Mathematics

6 answers

Yes.

So, g(3a) = -2(3a) - 1 = -6a - 1

2007-05-25 07:51:39 · answer #1 · answered by not gh3y 3 · 1 0

g(3a) = –2(3a) – 1 = -6a - 1

2007-05-25 08:07:33 · answer #2 · answered by Ana 4 · 0 0

yes

g(3a) = -2(3a) - 1

= -6a -1

2007-05-25 07:55:21 · answer #3 · answered by Trini 3 · 0 0

g( 3a) = -2(3a)-1
= -6a -1

2007-05-25 08:05:07 · answer #4 · answered by muhamed a 4 · 0 0

Yes!
g(3a) = - 2.(3a) - 1
g(3a) = - 6a - 1

2007-05-26 00:01:49 · answer #5 · answered by Como 7 · 0 0

Yep

2007-05-25 07:52:55 · answer #6 · answered by mark r 4 · 0 0

fedest.com, questions and answers